Osteophytes, Enthesophytes, and High Bone Mass: A Bone‐Forming Triad With Potential Relevance in Osteoarthritis. Issue 9 (September 2014) - Hardcastle, Sarah A.; Dieppe, Paul; Gregson, Celia L.; Arden, Nigel K.; Spector, Tim D.; Hart, Deborah J.; Edwards, Mark H.; Dennison, Elaine M.; Cooper, Cyrus; Williams, Martin; Davey Smith, George; Tobias, Jon H.
<x xml:space="preserve">Abstract</x> Objective Previous studies of skeletal remains have suggested that both enthesophytes and osteophytes are manifestations of an underlying bone‐forming tendency. A greater prevalence of osteophytes has been observed among individuals with high bone mass (HBM) compared with controls. This study was undertaken to examine the possible interrelationships between bone mass, enthesophytes, and osteophytes in a population of individuals with extreme HBM. Methods Cases of HBM (defined according to bone mineral density [BMD] Z scores on dual x‐ray absorptiometry) from the UK‐based HBM study were compared with a control group comprising unaffected family members and general population controls from the Chingford and Hertfordshire cohort studies. Pelvic radiographs from cases and controls were pooled and evaluated, in a blinded manner, by a single observer, who performed semiquantitative grading of the radiographs for the presence and severity of osteophytes and enthesophytes (score range 0–3 for each). Logistic regression analysis was used to identify significant associations, with a priori adjustment for age, sex, and body mass index. Results In this study, 226 radiographs from HBM cases and 437 radiographs from control subjects were included. Enthesophytes (grade ≥1) and moderate enthesophytes (grade ≥2) were more prevalent in HBM cases compared with controls (adjusted odds ratio [OR] 3.00 [95% confidence interval (95% CI) 1.96–4.58], P < 0.001 for any enthesophyte; adjusted OR 4.33 [95% CI 2.67–7.02], P < 0.001 for moderate enthesophytes). In the combined population of cases and controls, the enthesophyte grade was positively associated with BMD at both the total hip and lumbar spine (adjusted P for trend < 0.001). In addition, a positive association between osteophytes and enthesophytes was observed; for each unit increase in enthesophyte grade, the odds of any osteophyte being present were increased >2‐fold (P < 0.001). Conclusion Strong interrelationships were observed between osteophytes, enthesophytes, and HBM, which may be helpful in defining a distinct subset of patients with osteoarthritis characterized by excess bone formation.